Teachers Readiness in Implementing The Independent Curriculum at SD Xaverius 1 Palembang - Theresia Endang; Ria Triayomi; Modestha Modestha (International Journal on Advanced Science, Education, and Religion, 2022)
The research aims to find out how the teacher's readiness is in implementing the Independent Curriculum at SD Xaverius 1 Palembang. The teacher's readiness to implement the independent curriculum consists of four indicators of teacher readiness, namely pedagogic competence, personal competence, social competence and professional competence. This study used a qualitative research method with a descriptive approach. The research subjects consisted of class I and IV teachers. Data collection techniques used in this study consisted of interviews, questionnaires and documentation which were carried out in depth and systematically. The interview instrument used was 12 questions. The results of the study can be concluded that teacher readiness has been carried out well. This can be proven by looking at the implementation of pedagogic, personality, social and professional competencies to be able to meet and understand teacher competency indicator standards. Furthermore, there is good collaboration between related parties, namely the Office of Education, Principals and infrastructure to support Teachers in implementing the Independent Curriculum. Keywords: Teacher Readiness, Independent Curriculum, Implementing Independent Curriculum